Pilot study of the dynamics of emotional state and quality of life of patients in stage 2 of medical rehabilitation after acute COVID-19 - P. M. Demidov; M. V. Iakovleva; I. A. Zelenskaya; E. A. Demchenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The COVID-19 pandemic has had an enormous impact on public health and many other social institutions. Although the disease continues evolving, new strains do not exhibit the previous lethality, and coronavirus limitations are being lifted, the problem is still relevant. An important aspect of the study of COVID-19 is the process of patient recovery, including inpatient rehabilitation programs. The aim of this pilot study was to examine the psychosocial characteristics and dynamics of the indicators of emotional state (anxiety, depression) and quality of life in patients undergoing a medical rehabilitation program after COVID-19 (N=36; mean age 63.72±12.78 years; 33.33% male, 66.67% female).Research methods included a structured interview to collect data on patients’ sociodemographic and psychosocial characteristics, the State-Trait Anxiety Inventory (STAI), the Beck’s Depression Inventory (BDI), and the 36-Item Short Health Survey (SF-36). The patients were found to have an objective perception of their physical condition, with a lack of awareness of both the disease and the rehabilitation; the illness and recovery situation was markedly stressful for the patients. During the in-patient rehabilitation period, there was a positive change in state anxiety, depressive symptoms and quality of life (p<0.001). The dynamics of the specified characteristics almost do not differ in groups of male and female patients, except for indicators of anxiety, in which differences before and after rehabilitation are more expressed among women. The findings can be used to assess the effectiveness of rehabilitation programs and to improve it, and also indicate the primary role of the clinical psychologist in managing this group of patients.